Sequence of Volcanic Activity of Sakurajima Volcano, Japan, as Revealed by Non-Eruptive Deflation - Iguchi, Masato; Yamada, Taishi; Tameguri, Takeshi (Frontiers in Earth Science, 2022)
Since 1955, the Sakurajima volcano has experienced repeated Vulcanian eruptions accompanied by intense air-shocks, large ash clouds, and deflation ground deformations. However, ground deflations sometimes occurred even if no eruption took place. In this study, we categorize deflation events contained in continuous deformation records covering eruptive activities at the Sakurajima volcano Minamidake crater during the period from November 2017 to December 2020. The deflation events are classified into eruptive deflation and non-eruptive deflation (NED) types by examining the seismic data, infrasound generations, and visual phenomena. Their event type occurrence characteristics are then further clarified based on their relationships to pressure source volume changes. Comparing the pressure source volume changes with the monthly mass of volcanic ash expelled from the crater, which is estimated from deposition data around the volcano, we found the contribution of NED events to volcanic ash mass eruption amounts to be much smaller than that for Vulcanian events, and visual observations confirm that NED events are phenomena that primarily emit volcanic gas. The NED event changes during the episode are interpreted by the magna transition from bubble-rich to bubble-poor conditions and are supported by the sulfur dioxide (SO2) discharge rate.